‘Sentimental’: Since the Death of Little Nell - Dominic Rainsford (Cahiers Victoriens et Edouardiens)
This paper revisits the question of sentimentality in Dickens, particularly with reference to the frequently derided character of Little Nell in The Old Curiosity Shop. Sentimentality is discussed as a problematical critical term which attained negative connotations through the work of writers such as I. A. Richards, T. S. Eliot and F. R. Leavis, within the specific literary, social and political circumstances of the early- and mid-twentieth century, and which may be due for reconsideration now, in the wake of the ‘ethical turn’ in criticism which marked the century’s closing decades. Dickens often situates and frames sentimental feeling critically within The Old Curiosity Shop, while not suggesting that it should or even can be transcended by the ‘simple fellows’ that we all ultimately are (in Dickens’s view), given the impossible problems with which life confronts us. In this respect Dickens anticipates recent philosophical claims that some types of sentimentality cannot be avoided and should not be condemned.